Mn vaporization control and stress-induced martensite transformation in high-manganese steel welds under different laser keyhole conditions - Myeonghwan Choi; Daewon Cho; Kwang-Hyeon Lee; Namhyun Kang (Journal of Materials Research and Technology)
Vaporization modeling of high-Mn steel during laser welding, along with the effects of Mn vaporization on the tensile properties at room and cryogenic temperatures, were investigated for various laser defocusing (LD) conditions. The LD10 exhibited a full penetration keyhole, while LD20 showed a partial penetration keyhole. The vaporization modeling based on computational fluid dynamics (CFD) analysis confirmed that a significant Mn flux occurred in LD20, which corresponded with the most substantial loss of Mn observed in the partially penetrated weld. The room temperature tensile testing showed a slight increase in the yield strength and a minor reduction in tensile elongation for LD20, which could be attributed to the stress-induced ε-martensitic transformation. In cryogenic tensile testing, LD20 exhibited a higher yield strength with more martensitic transformation, including some stress-induced α′-martensitic transformation observed. Through the vaporisztion modeling, significant Mn vaporization in LD20 was found to decrease the stacking fault energy, which enhanced stress-induced martensite transformation and yielding stress during tensile deformation at 110 and 298 K.